Derivative Synonyms (Derivative Variants) of the Names of Persons Possessing Nominal Characteristics - Gaudinskaitė, Danguolė (Acta humanitarica academiae Saulensis, 2025)
In the Lithuanian language, the persons can be named by synonymous words (simple words and derivatives). A variety is revealed by lexical, derivative, syntactical synonyms as well as other language means. Derivative synonyms, which are one of the type of synonyms, are such derivatives of the Lithuanian language that have the same root, the same derivative meaning, but which are formed with different derivative means. Derivative variants should be distinguished from derivative synonyms: they are the derivatives formed from the same underlying word (or from the same underlying words) with the same derivative formative. They are formed by means of secondary derivative means, i.e. a vowel or a consonant of the root, variation of prefix, a connecting vowel, etc. The nominal derivatives indicating persons fall into five categories of noun formation. According to the features of the underlying words given to a derivative as well as derivative and lexical meanings, the compounds and derivatives with prefixes have synonymic relationship with the suffix and ending derivatives of traditional derivational categories. Applying the methods of derivative and semantic analysis as well as statistical, descriptive analytical, substitution methods, the derivatives of one derivative category – the names of the persons possessing nominal features – are discussed in the present article. The derivatives were drawn from LKŽ and LKŽe: 2,894 derivatives were selected, out of them 704 rows of derivative synonyms (derivative variants) were formed. Analysing the collected examples, it was revealed that the rows of derivative synonyms (derivative variants) can be divided into semantic groups according to some part of the body, similarity, character feature, etc. (barzdainis – barzdyla / barzdila – barzdylis – barzdylius – 2 barzdočius, -ė – barzdotis, -ė – barzdokas, -ė – barzdolė – barzdonas 1 – barzdukas 1 – barzduolis, -ė – barzdžius – velniabarzdis); according to family or mutual relationship (gentainis, -ė – gentininkas – gentaitis – gentbrolis); according to the meeting or gathering of people, participation in some joint events (vestuvininkas / vestuvinykas, -ė); according to inclination to one or another behaviour (juokininkas / juokinykas – juokorius – juokadaris, -ė / juokdarys, -ė / juokdaris, -ė / juokadara – juokbernis); according to favourite meal, drink or a person (druskininkas, -ė / druskinykas, -ė 2 – druskius, -ė – druskis, -ė); according to the place of participation somewhere, place of work (girtuvininkas, -ė / girtuvinykas, -ė / girtuvninkas, -ė / girtuvnykas, -ė); according to a person (or group of people), an organization, whose supporter or follower is a person (varpietis, -ė – varpininkas, -ė 2); according to a disease or an unhealthy part of the body (raupsuočius, -ė – raupsuotis, -ė); according to the received award or an achieved result (pirmūnas, -ė – pirmuolis, -ė); according to the work or rest time (2 nakti̇nis, -ė 2 – naktinyčia 8 – naktadarbis, -ė – nakti̇bauža 2 – 2 nakti̇žibis, -ė / nakti̇žiba – ži̇banaktis). The biggest part of derivatives is composed of derivatives with the suffixes (they make 70 per cent of the total number of all derivatives).
Keywords: formation; derivative synonyms; derivative variants; derivational categories; row of the synonyms